“CATAStrophy,” a Genome-Informed Trophic Classification of Filamentous Plant Pathogens – How Many Different Types of Filamentous Plant Pathogens Are There? - Hane, James K.; Paxman, Jonathan; Jones, Darcy A. B.; Oliver, Richard P.; de Wit, Pierre (Frontiers in Microbiology, 2020)
The traditional classification of fungal and oomycete phytopathogens into three classes,biotrophs, hemibiotrophs or necrotrophs, is unsustainable. This study highlights multiple phytopathogen species for which these labels have been inappropriately applied. We propose a novel and reproducible classification based solely on genome-derived analysis of carbohydrate active enzyme gene content called CAZyme-Assisted Training And Sorting of -trophy (CATAStrophy). CATAStrophy defines four major divisions for species associated with living plants. These are monomertrophs (corresponding to biotrophs), polymertrophs (corresponding to necrotrophs), mesotrophs (corresponding to hemibiotrophs), and vasculartrophs (including species commonly described as wilts, rots or anthracnoses). The monomertroph class encompasses symbiont, haustorial and non-haustorial species. Mesotrophs are divided into the subclasses intracellular and extracellular mesotrophs, and the polymertrophs into broad and narrow host sub-classes. This gives a total of seven discrete plant-pathogenic classes. The classification provides insight into the properties of these species and offers a facile route to develop control measures for newly recognised diseases. Software for CATAStrophy is available at https://effectordb.com. We present the CATAStrophy method for the prediction of trophic phenotypes based on CAZyme gene content, as a complementary method to the traditional tripartite ‘biotroph-hemibiotroph-necrotroph’ classifications that may encourage renewed investigation and revision within the fungal biology community.